PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MEMPERBAIKI PROSES PEMBELAJARAN DAN MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII 8 SMPN 25 PEKANBARU - Rima Tertia Putri; Titi Solfitri; Syofni Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics outcomes by applied the learning model of Problem Based Learning. The subject of this research is students in VII 8 class of SMPN 25 Pekanbaru in academic years 2017/2018, which amounted to 36 students. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative descriptive, while the students mathematic tests were analyzed in statistic quantitative descriptive. The qualitative descriptive showed an improvement of learning process from before the action to the first and second cycle. Most of students were very confidenced and actived in learning process, such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning.The results of this research showed the number of students that reach Minimum Mastery Criteria for knowledge increase from the basic score (33,33%) to (44,44%) at the first test and to (77,78%) at the second test. For the skills, the score increase from (58,33%) at the first test, to (80,56%) at the second test. The results of this research showed that appication of PBL can improve learning process and increase mathematics outcomes for students in VII 8 class of SMPN 25 Pekanbaru in academic years 2017/2018 for the subject matter Circumference and Area Quadrilaterals Triangles.Keywords : Mathematics Outcomes, Problem Based Learning